Pelaksanaan Program Gerakan Literasi Sekolah Pada Pembelajaran IPS di SMP Negeri 2 Batujajar ( Studi Deskriptif di Kelas VII Terhadap Pelaksanaan Program Gerakan Literasi Sekolah) - Wulandari, Mutiani Asri; Soemantri, Yeni Kurniawati; Rakhman, Muhammad Arief (Peneliti.net, 2024)
Social studies learning is one of the learnings that requires literacy skills, but the literacy skills possessed by students are still low so it requires the School Literacy Movement (GLS). The focus of the problem in this study is to see how the School Literacy Movement Program in social studies learning. This study aims to determine the implementation of the School Literacy Movement Program (GLS) for grade VII students at SMP Negeri 2 Batujajar, especially in social studies learning. The approach to this research is to use a qualitative research approach with a descriptive method. Data collection techniques use observation, interviews, and documentation studies. The results showed that there are 4 Literacy Movement Programs in SMP Negeri 2 Batujajar, namely the Readhaton Program, Book Grants, KERPUS, and Class Library. The implementation of these programs has not been optimally implemented by the school due to obstacles both from inside and outside the school. Similarly, the implementation of the Literacy Movement Program in social studies learning is still not optimal due to various obstacles and also the lack of teachers in integrating literacy programs in social studies subjects. Therefore, there must be some improvements from the programs that have been implemented by schools to improve the literacy ability of students to be better.